PENGEMBANGAN MULTIMEDIA INTERAKTIF PADA MATERI PERTUMBUHAN DAN PERKEMBANGAN MAKHLUK HIDUP UNTUK KELAS XI SMA - Ghearika Ghearika (UNM Journal of Biological Education, 2021)
Interactive multimedia of living things growth and development was developed with the aim of producing learning media that is interactive multimedia which is valid and practical. Interactive multimedia developed the form of mind maps that are in development using mindjet mindmanager application. This research is a type of Research and Development (R&D) using ADDIE development model, which has included analysis, design, development, implementation, and evaluation. The subject of this research was expert lecturers as subjects who assessed the research tools and tested the validity of interactive multimedia, biology teacher and student of XII MIA 5 at SMAN 14 Gowa as the subject who tested the practicality of interactive multimedia. Research result showed that interactive multimedia is valid and practical. The validity value obtained 96.78% (very valid), while the practicality value obtained from teacher’s response is 96.59% (very practical), and the practicality value obtained from student’s response is 86.33% (very practical). So that, it can be concluded that the interactive multimedia learning media that developed were suitable to use.